Preoperative factors predicting the severity of BMD loss around the implant after Total hip Arthroplasty - Morita, Akira (BMC Musculoskelet Disord, 2021)
BACKGROUND: Stress shielding after total hip arthroplasty (THA) leads to loss of bone mineral density (BMD) around the femoral implants, particularly in the proximal area. Loss of BMD around the implant is likely to occur within 1 year after THA; however, its severity depends on patient characteristics. This study evaluated preoperative factors correlated with the severity of zone 7 BMD loss after THA. METHODS: This retrospective cohort study included 48 patients who underwent primary THA from October 2011 to December 2015. All patients underwent implantation of a Zweymüller-type femoral component without any postoperative osteoporosis medications. The objective variable was a change in zone 7 BMD after 1 year. Factors evaluated included age, body mass index, Japanese Orthopaedic Association score, Harris Hip Score, Canal Flare Index (CFI), and lumbar BMD on the frontal and lateral sides. Univariate and multivariate regression analyses identified factors correlated with loss of zone 7 BMD. RESULTS: Univariate regression analysis identified CFI (P = 0.003) and preoperative lumbar BMD on the anterior-posterior (P = 0.003) and lateral (P < 0.001) sides as being correlated with loss of zone 7 BMD. Multivariate regression analysis identified CFI (P = 0.014) and lumbar BMD on the lateral side (P < 0.001) as being correlated independently with loss of zone 7 BMD. CONCLUSION: Lower preoperative lumbar BMD on the lateral side and lower CFI were correlated with zone 7 BMD loss after THA. Patients with these characteristics should be monitored carefully for severe BMD loss after THA.